Diagnostic role of 18F-FECH-PET/CT compared with bone scan in evaluating the prostate cancer patients referring with biochemical recurrence - Takesh, Mustafa; Odat Allh, Khaldoun; Zechmann, Christian (ISRN oncology, 2012)
18F-FECH-PET/CT has been proved to be an imaging agent for prostate carcinoma. However, its role in detecting the bone metastases is still blurred owing to the lack of related studies. The purpose of our study was to assess the efficacy of PET with 18F-ethylcholine in assessing the bone status and to compare the results with that of conventional bone scan findings. For this purpose, we selected 37 patients (mean age ), who had been referred for restaging purposes due to biochemical recurrences and underwent both 18F-FECH-PET/CT and bone scan in a short interval. Generally 18 patients out 37 patients referred with biochemical relapse were confirmed to have bone involvement. From 18 confirmed bone involvement cases, 18F-FECH-PET/CT identified correctly the bone involvement in 15 cases with overall sensitivity of 83.3%. On the other hand, bone scan identified 17 out of 18 confirmed cases with overall sensitivity of 94.4%. The lesion-related results show that the sensitivity of each investigation differs with the anatomical regions, and by comparing both results, 18F-FECH-PET/CT was mostly superior to bone scan; however, without a statistical significance (). In conclusion, no significant gain in sensitivity was achieved using bone scan compared with 18F-FECH-PET/CT.